How Medical Error Shapes Physicians' Perceptions of Learning: An Exploratory Study. (August 2019) - Shepherd, Lisa; LaDonna, Kori A.; Cristancho, Sayra M.; Chahine, Saad
Abstract : Purpose: Error is inevitable in medicine, given its inherent uncertainty and complexity. Errors can teach powerful lessons; however, because of physicians' self-imposed silence and the intricacies of responsibility and blame, learning from medical error has been underexplored. The purpose of this study was to understand how physicians perceived learning from medical errors by exploring the tension between responsibility and blame and factors that affected physicians' learning. Method: Nineteen physicians participated in semistructured interviews, conducted in 2016–2017 at Western University in Canada, that probed their experiences in learning from medical errors. Data collection and analysis were conducted iteratively, with themes identified through constant comparative analysis. Results: Participants felt personal responsibility and blame for their errors. Residency produced particularly salient memories of errors. Participants identified interconnecting cultural factors (normalizing error, peer support and mentorship, formal rounds) and individual factors (emotional response, confidence and experience), which either helped or hindered their perceived learning. Conclusions: Learning from medical error requires navigation through blame and responsibility. The keen responsibility felt by physicians must be acknowledged when enacting a system-based approach to medical error. Adopting a learning culture perspective suggests opportunities to enable and disable features of the learning environment to optimize learning from error as residents learn to become the most responsible physician for all outcomes. A better understanding of the factors that shape learning from error can help make the transition from error to learning more explicit, thereby increasing the opportunity to learn and teach from errors that permeate the practice of medicine.